Fighting Strategies Against the Novel Coronavirus Pandemic: Impact on Global Economy - Gorain, Bapi; Choudhury, Hira; Molugulu, Nagashekhara; Athawale, Rajani B.; Kesharwani, Prashant (Frontiers in Public Health, 2020)
Sudden outbreak of a new pathogen in numbers of pneumonic patients in Wuhan province during December 2019 has threatened the world population within a short period of its occurrence. This respiratory tract isolated pathogen was initially named as novel coronavirus 2019 (nCoV-2019), however, later termed as SARS-CoV-2. The rapid spreading of this infectious disease received the label of pandemic by the WHO within four months of its occurrence, which still seeks continuous attention of the researchers to prevent the spread and cure of the infected patients. The propagation of the disease has been recorded in 215 countries with more than 25.5 million cases with a death toll of more than 0.85 million. Several measures are taken to control the disease transmission and researchers are actively engaged in finding suitable therapeutics to effectively control the disease to minimize the mortality and morbidity rates. Several existing potential candidates were explored in the prevention and treatment of worsening condition of COVID-19 patients; however, none of the formulation got approval for the treatment but used under medical supervision. In this article, a focus has been made to highlight on current epidemiology on the COVID-19 infection, clinical features, diagnosis and transmission; with special emphasis on treatment measures of the disease at different stages of clinical research and the global economic influence due this pandemic situation. Progress in the development on vaccine against COVID-19 has also been explored as important measures to immunize people. Moreover, this article is expected to provide information to the researchers who are constantly combating in the management against this outbreak.